The Reality of Smoke-Free Area Policy in Healthcare: "Case Study in The Special Lung Hospital of North Sumatra Province, Medan, Indonesia" - Tarigan, Frida Lina; Purba, Ivan Elisabeth; Zega, Winar Purnawan Sari; Harianja, Ester; Nababan, Donal (Journal of Health Education, 2025)
Background: The Special Lung Hospital of North Sumatra Province, Medan, Indonesia is mandated by city regulations to implement the Smoke-Free Area (SFA) policy. In the fact, smoking by visitors and security personnel still occurs, posing health risks to patients and staffs. However, smoking activities by visitors and security staff were observed, posing health risks to patients and mployees. This study aims to analyse the implementation, challenges, and possible solutions related to the SFA policy. Methods:  Using a qualitative case study design, six informants were interviewed, including the Hospital Director, Health Safety Environment Committee, security staff, employees, cleaning staff, and visitors. Data were collected through interviews, observations, and documentation, with triangulation used to ensure validity. Result: The study indicates that, although the policy has been implemented, its effectiveness remains limited due to weak communication, insufficient resources, a lack of commitment, and an inadequate bureaucratic structure. Major obstacles include poor coordination with the government in Medan, limited no-smoking signage, low compliance and awareness among staffs, a lack of a dedicated task force, and weak law enforcement without clear sanctions. Conclusion: Additionally, socialization and outreach regarding SFA regulations remain minimal. To strengthen implementation, proposed solutions include improving interagency communication, enhancing enforcement and signage, issuing a director's circular, reactivating cessation clinics, and fostering collaboration among hospital units to promote and supervise continuous SFA